2022
DOI: 10.1002/ps.6934
|View full text |Cite
|
Sign up to set email alerts
|

Penetrance during Wolbachia‐mediated parthenogenesis of Trichogramma wasps is reduced by continuous oviposition, associated with exhaustion of Wolbachia titers in ovary and offspring eggs

Abstract: BACKGROUND: Thelytokous Wolbachia-infected Trichogramma wasps are superior to bisexual uninfected wasps regarding biological control programs. However, continuous oviposition weakens the parthenogenesis-inducing (PI) strength of Wolbachia. Whether this reduced PI strength relates to decreases in the titer of Wolbachia in the ovary and offspring eggs of Trichogramma remains unclear. Here, using fluorescence in situ hybridization (FISH) and reverse transcription quantitative polymerase chain reaction (RT-qPCR) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…It is worth noting that Wolbachia signals in adult heads were weak. Similarly, our previous study also found that Wolbachia density was low in the heads of Trichogramma pretiosum and T. dendrolimi based on qPCR and Fish detection ( 39 ). Though Wolbachia signals were weak in adult heads, we still detected a significant downregulation of memory-related gene expression in infected adults compared with their uninfected counterparts.…”
Section: Discussionsupporting
confidence: 60%
“…It is worth noting that Wolbachia signals in adult heads were weak. Similarly, our previous study also found that Wolbachia density was low in the heads of Trichogramma pretiosum and T. dendrolimi based on qPCR and Fish detection ( 39 ). Though Wolbachia signals were weak in adult heads, we still detected a significant downregulation of memory-related gene expression in infected adults compared with their uninfected counterparts.…”
Section: Discussionsupporting
confidence: 60%
“…However, no Wolbachia signals were detected in the heads of pupal or adult T. dendrolimi and T. pretiosum . Our previous study revealed that Wolbachia infection caused memory loss, increased the incidence of superparasitism, and attenuated the host discrimination mechanism in T. dendrolimi ( Zhou et al., 2022a ). Though the Wolbachia titers in the heads of Trichogramma adults were low, the endosymbiont nonetheless caused behavioral changes in the wasps.…”
Section: Discussionmentioning
confidence: 98%
“…The PI strength in Trichogramma wasps is strongly influenced by Wolbachia density in the germ line and eggs. Previous studies showed that weak PI strength is often associated with biotic (e.g., continuous oviposition) or abiotic (e.g., high temperature) factors that can affect the transmission rate of Wolbachia ( Zhou et al., 2022a ; Guo et al., 2023 ). The unstable PI strength of Wolbachia -infected Trichogramma can impact the quality of Trichogramma offspring and their efficacy in pest control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations